2009
DOI: 10.1086/606162
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Lock Technique: Review of the Literature

Abstract: Central venous catheters (CVCs) are commonly used among adult and pediatric patients for administration of fluids, medications, and nutrition. Central line-associated (CLA) bloodstream infection (BSI) is a serious complication following CVC insertion. The aim of this review is to summarize available data regarding the ethanol lock technique, which is a proposed method for sterilizing the lumen of the catheter by instilling an ethanol solution and allowing it to dwell in the catheter for a certain amount of tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 48 publications
0
53
0
6
Order By: Relevance
“…Hemmelgarn et al reported successful reduction in CRBSI with the use of once-weekly tissue plasminogen activator, but the longterm cost of this strategy is prohibitive (32). Ethanol locking solutions are effective sterilizing agents for CRBSI prophylaxis, as well as for salvage in silicone-based central venous catheters of oncology patients and pediatric patients receiving parenteral nutrition (33). However, safety of ethanol in polyurethane-based hemodialysis catheters has been an ongoing concern.…”
mentioning
confidence: 99%
“…Hemmelgarn et al reported successful reduction in CRBSI with the use of once-weekly tissue plasminogen activator, but the longterm cost of this strategy is prohibitive (32). Ethanol locking solutions are effective sterilizing agents for CRBSI prophylaxis, as well as for salvage in silicone-based central venous catheters of oncology patients and pediatric patients receiving parenteral nutrition (33). However, safety of ethanol in polyurethane-based hemodialysis catheters has been an ongoing concern.…”
mentioning
confidence: 99%
“…Resistance to the bactericidal effect does not develop because it exerts its effect via nonspecific protein denaturation in the cell wall of the microorganism (27). Thirty percent and higher concentrations of ethanol show a bactericidal effect on S. aureus (26).…”
Section: Arıkan T Et Al: Effect Of Catheter Locking Solution Consistimentioning
confidence: 96%
“…Ethanol is a cheap, broad-spectrum antiseptic and disinfectant agent and has bactericidal effect for both Gram-positive and Gramnegative organisms as well as a fungicidal effect (26). Resistance to the bactericidal effect does not develop because it exerts its effect via nonspecific protein denaturation in the cell wall of the microorganism (27).…”
Section: Arıkan T Et Al: Effect Of Catheter Locking Solution Consistimentioning
confidence: 99%
“…Se realizaron 5 diluciones: 10, 30, 50, 70 y 90% (v/v) con etanol al 25% (Maiefski et al, 2009). Se transfirió 1 ml del inóculo estandarizado más 1 ml de las cinco concentraciones del aceite esencial de canela de cada una de las cepas y se incubaron a 37 °C durante 24 h, estableciendo la concentración mínima inhibitoria (CMI).…”
Section: Aceite Esencial De Canela -Cmi Y Cmbunclassified